2017
DOI: 10.5812/jjm.13368
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Pattern and Prevalence of Extended-Spectrum β-Lactamase Genotypes among Clinical Isolates of Acinetobacter baumanii in Tabriz, North-West of Iran

Abstract: Background: Multidrug resistant (MDR) Acinetobacter baumanii strains have emerged as novel nosocomial pathogens threaten-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In one study in Iran, the prevalence of blaTEM and blaCTX genes was 52.1% and 43.4%, respectively, in ESBL-producing A. baumannii isolates (36). Two other studies also reported the presence of blaCTX-M and blaTEM genes in clinical isolated of ESBL-producing A. baumannii isolates (34,37). In 2019, 42% of A. baumannii strains isolated from patients admitted to hospitals in Tehran were positive for the blaTEM gene and negative for the presence of the blaSHV gene (33).…”
Section: Discussionmentioning
confidence: 98%
“…In one study in Iran, the prevalence of blaTEM and blaCTX genes was 52.1% and 43.4%, respectively, in ESBL-producing A. baumannii isolates (36). Two other studies also reported the presence of blaCTX-M and blaTEM genes in clinical isolated of ESBL-producing A. baumannii isolates (34,37). In 2019, 42% of A. baumannii strains isolated from patients admitted to hospitals in Tehran were positive for the blaTEM gene and negative for the presence of the blaSHV gene (33).…”
Section: Discussionmentioning
confidence: 98%